Effects of electron-phonon intervalley scattering and band non-parabolicity on electron transport properties of high-temperature phase SnSe: An ab initio study. (January 2022) - Zhou, Wenjiang; Dai, Yu; Liu, Te-Huan; Yang, Ronggui
Abstract: High-temperature phase tin selenide ( β -SnSe) possesses a large power factor owing to its innately complex band structure. A detailed analysis of the electron-phonon (e-ph) intervalley scattering between the different non-parabolic valleys in β -SnSe remains to be disclosed. Using ab initio approach, the phonon-limited carrier mobility, Seebeck coefficient, and power factor in the range from 800 to 950 K were calculated. The e-ph intervalley scattering was shown to drastically increase the electron scattering rates, particularly in the processes involving acoustic or transverse-optical phonons. This scattering suppresses the mean free path of holes and electrons to less than 2 nm, which is detrimental to the power factor. As the temperature increases, the hole and electron mobilities decrease with the relations from T −2.38 to T −3.47 in different crystallographic directions, the values which drop much faster than the predictions given by the typical T −1.5 dependence, partly because of the high non-parabolicity of the band structure. This study highlights the necessity of explicitly considering the synergetic effect from the e-ph intervalley scattering and band non-parabolicity when modeling the electron transport of β -SnSe. Graphical abstract: Image 1 Highlights: The phonon-limited carrier mobility, Seebeck coefficient, and power factor of β -SnSe are studied using ab initio approaches. The intervalley scattering drastically increases the scattering rates and suppresses the mean free paths to less than 2 nm. Partly due to the highly non-parabolic band structure, the carrier mobilities largely deviate from the typical T −1.5 law. The power factor is mainly contributed by the carriers with the mean free paths between 2 and 10 nm.